Primary malignant achromic melanoma of the lung. Issue 1 (January 2014) - Lazarou, Ilias; Purek, Lesek; Duc, Christophe; Licker, Marc‐Joseph; Spiliopoulos, Anastase; Tschopp, Jean‐Marie
Abstract Currently, less than thirty cases of primary malignant melanoma of the lung have been reported in the literature. Thus, strict criteria for diagnosis have been published and include: malignant melanoma associated with bronchial epithelial changes; a solitary lung tumor; no prior history of skin, mucous membrane, intestinal or ocular melanoma; and absence of any other detectable tumor at the time of diagnosis. In this article we present a case of melanoma of the lung without evidence of extra‐pulmonary disease.